Evaluation of vitamin D and vitamin D-binding protein levels and vitamin D receptor expression in basal cell carcinoma: a case-control study - Noha Abdel-Rahim Nagui; Marwa A Saleh; Sherien M El-Daly; Nohha H Khater; Dina A El Sharkawy (Wolters Kluwer Medknow Publications, 2022)
Background Exposure to the sun is the main cause of basal cell carcinoma (BCC) development and also the main source of vitamin D in the body. Vitamin D has anticancer activities; however, its role in BCC is debatable. Objective To measure the level of plasma vitamin D, vitamin D-binding protein (VDBP), and vitamin D receptor (VDR) relative expression in BCC patients and healthy controls, in an attempt to evaluate their association with BCC development. Patients and methods Plasma vitamin D and VDBP as well as VDR relative expression levels were measured in 30 BCC patients and 30 healthy controls. VDR relative expression was also measured in nonlesional skin of patients and compared with that of lesional skin. Results Vitamin D, VDBP, and VDR expression levels were statistically significantly lower in BCC patients (16.8±9.65 ng/ml, 275.8±206.7 ng/ml, 0.49±0.35, respectively) than in controls (22.7±11.3 ng/ml, 429.7±248.1 ng/ml, 1.02±0.07, respectively) (P=0.027, 0.12, and 0.001, respectively). In addition, VDR relative expression was statistically significantly lower in BCC tissue than in nonlesional skin of patients (0.644±0.234) (P=0.001). Conclusion Decreased vitamin D, VDBP, and VDR expression levels may be associated with BCC, suggesting a possible role in the pathogenesis of the disease. Correction of vitamin D deficiency via supplementation or topical application of vitamin D analogs may have a role in the prevention or therapy of BCCs that should be evaluated.